[The Greeks] 'called it KOSMOS, which means ornament' - Kent Bloomer (Approaching Religion, 2016)
The title of this article is a statement quoted from a translation of The Etymologies of Isidore of Seville, 615–630 ad. The article proposes that the content of ornament is primordially derived from the eternal motions found in the macrocosm, a cosmology of ornament that looks beyond the extreme subjectivity that dominated modern art in the late twentieth century. The findings are rooted in the history and major theories of ornament, to be buttressed by examples of ornament-design throughout the ages. Finally, the article reviews the author’s own work in that light.